1976
DOI: 10.1111/j.1748-1716.1976.tb10203.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lesions in the Parabrachial Nucleus on the Mechanisms for Central and Reflex Termination of Inspiration in the Cat

Abstract: The effects of PCO2 and body temperature on the time course and peak amplitude of the central inspiratory activity (CIA) and the inspiratory "off-switch" threshold was studied in apneustic and non-apneustic cats. Apneusis resulted from lesions of the inspiratory inhibiting structures of the medial parabrachial nucleus (NPBM) and by interrupting vagal volume feedback. The cats were paralyzed and ventilated either proportionally to their phrenic output or at predetermined rate and volume. The dependence of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(41 citation statements)
references
References 28 publications
6
35
0
Order By: Relevance
“…An approximate indication of the 'vagal contribution' to inspiratory 'off-switch' (Euler & Trippenbach, 1976) Phro-Phrc (rel. units) VT eq (ml.)…”
Section: Timingmentioning
confidence: 99%
See 2 more Smart Citations
“…An approximate indication of the 'vagal contribution' to inspiratory 'off-switch' (Euler & Trippenbach, 1976) Phro-Phrc (rel. units) VT eq (ml.)…”
Section: Timingmentioning
confidence: 99%
“…4B shows that due to the decrease in respiratory rate 'demand' for ventilation was reduced more than PhrT when procaine was applied on the R(M) areas but less than PhrT when it was applied on the C(L) areas. (Euler & Trippenbach, 1976). In the absence of vagal volume feed-back GRADED BLOCK OF CENTRAL CHEMORECEPTORS the relationship between the effects on rate of rise of inspiratory activity and on inspiratory 'off-switch' thresholds, i.e.…”
Section: Effects Of Topical Applicadion Of Procainementioning
confidence: 99%
See 1 more Smart Citation
“…For the injured nervous system in man instability of rhythm leading to death is associated with lesions of the brain stem (Plum, 1970). Low decerebration (Lumsden, 1923;Stella, 1938), or bilateral lesions in the region of the nucleus parabrachialis, can cause prolonged periods of inspiratory 'apneusis' (Sears, 1977) in cats, rabbits and other mammalian species, but with intact vagi the rhythm is maintained through the reflex action (Breuer-Hering reflex) of the pulmonary stretch receptors (Euler, Martilla, Remmers & Trippenbach, 1976). Although infant breathing is episodic, particularly during REM sleep (Bryan & Bryan, 1979), it is essentially stable and following each apnoeic pause there is spontaneous resumption of the rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…Lesion studies have suggested that profound changes in respiration are organized within the pons and these observations led to schemes involving the description of pneumotaxic and apneustic centres within those pontine structures (see for example Euler, Martilla, Remmers & St John, 1972;Trippenbach, 1976). Anatomical tracing studies show that the pons, and particularly the parabrachial complex, is a target for descending inputs from the forebrain, hypothalamus, midbrain and cerebellum and also indirectly for reflex afferent inputs that arise from pulmonary and airway receptors, etc.…”
mentioning
confidence: 99%